La Place de l'État en Afrique selon la Banque mondiale : les limites d'une politique néo-libérale "amendée" - Nadir Altinok; Tarik Lakhal (Les éditions de la Maison des sciences de l'Homme, 2005)
This contribution aims to analyse the change in discourse held by the World Bank concerning the reform of the State in Africa in the educational sphere. After inspection, it emerges that despite new discourses on the "fight against poverty", the World Bank's neo-liberal policy still grants the State a minor role in the design and execution of educational policies. One would have thought of an evolution from the strict structural adjustment policies towards a policy of social adjustment where fundamental assets concerning the social field would be taken into account. That is not the case: the fight against poverty policy maintains the course of adjustment policies, by preserving a minimal social safety net.